2009
DOI: 10.1111/j.1398-9995.2008.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

Histamine N‐methyltransferase 939A>G polymorphism affects mRNA stability in patients with acetylsalicylic acid‐intolerant chronic urticaria

Abstract: The HNMT 939A>G polymorphism lowers HNMT enzymatic activity by decreasing HNMT mRNA stability, which leads to an increase in the histamine level and contributes to the development of AICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 31 publications
0
31
1
1
Order By: Relevance
“…1). Among the 42 selected studies that reported genetic predictors in association with immediate-type hypersensitivity, 19 were related to BLs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (Table 1), 12 to aspirin (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (Table 2), and eight to other NSAIDs (43-50) (Table 3). Three studies reported genetic predictors in association with biologicals, including hypersensitivity to asparaginase (51), EGF receptor inhibitors (52), and infliximab (53) ( Table 4).…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Among the 42 selected studies that reported genetic predictors in association with immediate-type hypersensitivity, 19 were related to BLs (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) (Table 1), 12 to aspirin (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) (Table 2), and eight to other NSAIDs (43-50) (Table 3). Three studies reported genetic predictors in association with biologicals, including hypersensitivity to asparaginase (51), EGF receptor inhibitors (52), and infliximab (53) ( Table 4).…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…They highlighted the involvement of genes that can be grouped into four pathogenic groups: (i) the membrane-spanning 4A gene family (FCER1A (formerly, FceR1a), MS4A2 (formerly, FceR1b), and FCER1G (formerly, FceR1c); (ii) the histamine production pathway (HNMT) (34,35,38); (iii) the inflammatory cytokines (TGFB1, TNF, and IL18) (36,37,40); and (iv) the arachidonic acid pathway (ALOX5, LTC4S, TBXA2R, and PTGER4) (33,39,41,42) (Table 2 Fig. 3).…”
Section: Genetic Predictors Of Nar To Aspirinmentioning
confidence: 99%
“…The histamine N-methyltransferase 939A>G polymorphism has been associated with NECD [108], suggesting that histamine-related genetic variants could have a role in crosshypersensitivity to NSAIDs, as occurs in allergies and other diseases [109]. However, in a previous study we did not find associations between NSAID-induced hypersensitivity and common SNPs for 3 histamine receptors [110], although we did find that the diamine oxidase (histaminase) missense polymorphism rs10156191 (Thr16Met), which affects histamine metabolism, was associated with NIUA and NERD [111].…”
Section: Other Variants Outside Eicosanoid Biosynthesismentioning
confidence: 99%
“…The histamine N-methyl transferase, HNMT 939A>C polymorphism was associated with the AICU phenotype by regulation of enzymatic activity and histamine release from peripheral basophils [30 ]. No significant associations were found between the two histamine receptor genes HRH1 and HRH2 and the AIU phenotype in a Korean population [34].…”
Section: Histamine-related Genesmentioning
confidence: 89%